Does Posterior Fixation of Partially Unstable Open-Book Pelvic Ring Injuries Decrease Symphyseal Plate Failure? A Biomechanical Study. (February 2018) - Metz, Rachelle M.; Bledsoe, J. Gary; Moed, Berton R.
Abstract : Objective: Recent clinical study suggests an advantage to adding an iliosacral screw to the anterior fixation construct for anteroposterior compression type-2 (OTA/AO type 61-B1), partially unstable open-book pelvic ring injuries. Others have described stress examination to determine any required supplemental fixation. However, biomechanical studies investigating iliosacral fixation requirements for this injury are lacking. Our objective was to determine whether adding an iliosacral screw to symphyseal plate fixation decreases displacement in a well-defined open-book pelvic ring injury model. Methods: An open-book pelvic ring injury was created in 10 human cadaveric pelves by unilaterally releasing the sacrospinous, sacrotuberous, and anterior sacroiliac ligaments plus transection of the pubic symphysis, approximating the classically described anteroposterior compression type-2 (APC-2) injury. Specimens were divided into 2 groups: (1) symphyseal plating and (2) plating plus an iliosacral screw. Using a standard bilateral stance model loaded at 550 N, displacement measurements were obtained at 210, 000 and 500, 000 cycles. Results: Three specimens failed before 210, 000 cycles because of technical errors and were excluded from analysis. For the remaining 7, there was no significant difference in displacement between the 2 groups, and none sustained implant failure. Post hoc analysis showed that a large sample size (45/group) would be required to detect any difference with 80% power, indicating a small effect size with limited clinical application. Conclusions: Adding an iliosacral screw to the symphyseal plate fixation does not provide improved biomechanical outcome in classically described APC-2 injuries. Clinically, stress examination may be useful to determine the need for supplemental posterior fixation in APC-2 injuries.